Rendezvous in cognitive radio ad hoc networks: a survey. (2018) - Ukey, Aishwarya Sagar Anand; Chawla, Meenu
Cognitive radio networks (CRNs) cope with spectrum scarcity and underutilisation problem through opportunistic sharing of spectrum and provide dynamic access to the free portions of spectrum allotted to licensed users. Fundamental step during the formation of CRN is the rendezvous process where secondary users (SUs) meet on commonly available channels and establish communication links for information exchange, spectrum management, and data communication. Non-availability of any prior network-related information and non-awareness of the presence of other SUs before the rendezvous process makes rendezvous a non-trivial task. Further, owing to the dynamics in licensed users' activity, diversities in the temporal and geographical location of SUs, absence of central authority, multi-hop architecture and mobility of SUs complicate the rendezvous process. This paper focuses on the taxonomy and challenges relevant to rendezvous phenomena of SUs and provides a brief overview and comparative qualitative analysis of the state-of-the-art rendezvous algorithms designed for CRNs.